2017
DOI: 10.1111/bph.13687
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial ROS generation mediates the loss of the anti‐contractile effects of perivascular adipose tissue in high‐fat diet obese mice

Abstract: BACKGROUND AND PURPOSEObesity is associated with structural and functional changes in perivascular adipose tissue (PVAT), favouring release of reactive oxygen species (ROS), vasoconstrictor and proinflammatory factors. The cytokine TNF-α induces vascular dysfunction and is produced by PVAT. We tested the hypothesis that obesity-associated PVAT dysfunction was mediated by augmented mitochondrial ROS (mROS) generation due to increased TNF-α production in this tissue. EXPERIMENTAL APPROACHC57Bl/6J and TNF-α recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 65 publications
(67 reference statements)
7
64
0
2
Order By: Relevance
“…Insulin sensitivity was calculated using the homeostasis model assessment-insulin resistance (HOMA-IR) index, which takes into account insulin and fasting blood glucose levels, using the following mathematical formula: HOMA-IR ϭ fasting insulin ϫ fasting glucose/22.5. Additional nutritional and metabolic information from the mouse models can be found in previous studies (6,7,42). At the end of treatment, animals were maintained under anesthesia with 2.5% isoflurane for blood collection and then culled by CO 2 inhalation.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin sensitivity was calculated using the homeostasis model assessment-insulin resistance (HOMA-IR) index, which takes into account insulin and fasting blood glucose levels, using the following mathematical formula: HOMA-IR ϭ fasting insulin ϫ fasting glucose/22.5. Additional nutritional and metabolic information from the mouse models can be found in previous studies (6,7,42). At the end of treatment, animals were maintained under anesthesia with 2.5% isoflurane for blood collection and then culled by CO 2 inhalation.…”
Section: Methodsmentioning
confidence: 99%
“…The most important role of PVAT is to reduce vasoconstrictive responses to noradrenaline or phenylephrine (PHE) by releasing various relaxation factors; this is called an anti‐contractile property . However, in obesity there are structural and functional changes in PVAT, which can result in vascular dysfunction by influencing endothelial and smooth muscle cells . Previously, we have shown that this anti‐contractile property of PVAT was abolished in obesity because of high free fatty acids (FFA), which attenuated the anti‐contractile response through an endothelium‐dependent pathway.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, in obesity there are structural and functional changes in PVAT, which can result in vascular dysfunction by influencing endothelial and smooth muscle cells. [5][6][7] Previously, we have shown that this anti-contractile property of PVAT was abolished in obesity because of high free fatty acids (FFA), which attenuated the anti-contractile response through an endothelium-dependent pathway. The mechanism involves an increase in inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a clear link between loss of anti‐contractile activity in obese murine aortic PVAT and increased mitochondrial ROS in the PVAT is shown by da Costa et al . () in this issue. Interestingly, in their study, obese mice lacking the TNF‐α receptor were protected from the deleterious effects of the high‐fat diet on PVAT function.…”
mentioning
confidence: 80%